Cultural atlas of Japan - Collcutt, Martin (1988)
This is an excellent general history ("for general readers and travelers"), authoritatively written and lavishly illustrated. As a cultural atlas, however, it is much less satisfying. Most of the nearly 60 maps are historical, and although cultural developments (especially those related to religion) are placed within the historical framework, there is a lack of focus on cultural matters. Many major literary and artistic figures are omitted. The third edition of H. Paul Varley's Japanese Culture (Univ. of Hawaii, 1984) is a much better cultural history, but both general and subject collections would benefit from the maps, illustrations, glossary, historical tables, and narrative provided in the Cultural Atlas of Japan .